"The 'blazer boys' were getting all the chances": South Asian men's experiences of cricket coaching in England. Issue 8 (24th July 2021) - Fletcher, Thomas; Piggott, David; North, Julian
Abstract: In the United Kingdom, recent research documents an over-representation of White participants, coaches, and decision makers within sporting contexts. In contrast Black, Asian and minority ethnic (BAME) groups are under-represented at all levels of sport: from players, coaches, and managers in sport governance. Recent research into the experiences of BAME men and women in sports coaching also shows that inclusive sporting environments, including a diverse workforce, are highly motivating for entry into, and progression through, the coaching pathway. However, significant and powerful barriers exist that prevent the progression of BAME individuals into higher level coaching qualifications and job roles. These barriers lead to the privileging of White men and are therefore described as both raced and gendered. This paper is based on a research project commissioned by the England and Wales Cricket Board in 2014 to explore South Asian male players' and coaches' experiences of coaching and progression through coaching pathways. We draw on data collected from 33 semi-structured interviews carried out with a sample of male South Asian players and coaches, from two different geographical areas - London and Yorkshire - and from a sample of clubs with different levels of ethnic diversity. Our analysis showed that South Asian players participate in an environment and culture where they are unlikely to engage in coaching and, even when they do, will not feel supported in progressing to higher roles of influence and power.